Geographic Variation in the Petiole–Lamina Relationship of 325 Eastern Qinghai–Tibetan Woody Species: Analysis in Three Dimensions - Li, Yanan; Kang, Xiaomei; Zhou, Jieyang; Zhao, Zhigang; Zhang, Shiting; Bu, Haiyan; Qi, Wei (Frontiers in Plant Science, 2021)
The petiole-lamina relationship is central to the functional tradeoff between photosynthetic efficiency and the support/protection cost. Understanding environmental gradients in the relationship and its underlying mechanisms remains a critical challenge for ecologists. We investigated possible scaling of the petiole-lamina relationships in three dimensions, i.e. petiole length (PL) vs. lamina length (LL), petiole cross-sectional area (PCA) vs. lamina area (LA), and petiole mass (PM) vs. lamina mass (LM), for 325 Qinghai-Tibetan woody species, and examined their relation to leaf form, altitude, and climate and vegetation types. Both cross-species analysis and meta analysis showed signiﬁcantly isometric, negatively allometric and positively allometric scaling of the petiole-lamina relationships in the length, area and mass dimensions, respectively, reflecting an equal, slower and faster variation in petiole than lamina in these trait dimensions. Along altitudinal gradients, the effect size of the petiole-lamina relationship decreased in the length and mass dimensions but increased in the area dimension, suggesting the importance in petiole development of enhancing leaf light-interception and nutrient transport efficiency in the warm zones, but enhancing leaf support/protection in the cold zones. The significant additional influences of LA, LM and LA were observed on the PL-LL, PCA-LA and PM-LM relationships, respectively, implying that the single-dimension petiole trait is affected simultaneously by the multi-dimensional lamina traits. Relative to simple-leaved species, the presence of petiolule in compound-leaved species can increase both leaf light interception and static gravity loads or dynamic drag forces on petiole, leading to lower dependence of petiole length variation on lamina length variation, but higher biomass allocation to petiole. Our study highlights the need for multi-dimension analyses of the petiole-lamina relationships, and illustrates the importance of plant functional tradeoffs and the change in the tradeoffs along environmental gradients in determining the relationships.